2016
DOI: 10.1080/00288330.2015.1132747
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic shorelines in New Zealand? Quantification and characterisation of microplastic pollution on Canterbury's coastlines

Abstract: Microplastics are persistent environmental contaminants found in marine environments worldwide. Microplastic particles isolated from coastlines in the Canterbury region of New Zealand were quantified and characterised. Sediment samples were collected from 10 locations representing exposed-beach, estuarine and harbour environments in both urban and non-urban settings. Particles were isolated from sediments using an NaCl densityseparation procedure and quantified and characterised with a combination of optical/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…Although visual confirmation techniques are inexpensive in terms of time and cost, misidentification of natural particles such as coal ash or coal fly (Eriksen et al ), quartz or calcium carbonate (Ballent et al ), or steric acid and castor oil (Ziajahromi et al ) is possible. Several authors have therefore concluded that the visual identification error rate for identifying natural particles as microplastics is unacceptably high, ranging from 33 to 70% (Hidalgo‐Ruz et al ; Dekiff et al ; Lenz et al ; Lusher et al ; Ballent et al ; Clunies‐Ross et al ; Fischer et al ; Horton et al ; Imhof et al ; Kanhai et al ). Studies not using appropriate analytical confirmation techniques are likely overestimating environmental concentrations of relevant size fractions (Lusher et al ).…”
Section: Sources and Occurrence Of Microplastics In The Environmentmentioning
confidence: 99%
“…Although visual confirmation techniques are inexpensive in terms of time and cost, misidentification of natural particles such as coal ash or coal fly (Eriksen et al ), quartz or calcium carbonate (Ballent et al ), or steric acid and castor oil (Ziajahromi et al ) is possible. Several authors have therefore concluded that the visual identification error rate for identifying natural particles as microplastics is unacceptably high, ranging from 33 to 70% (Hidalgo‐Ruz et al ; Dekiff et al ; Lenz et al ; Lusher et al ; Ballent et al ; Clunies‐Ross et al ; Fischer et al ; Horton et al ; Imhof et al ; Kanhai et al ). Studies not using appropriate analytical confirmation techniques are likely overestimating environmental concentrations of relevant size fractions (Lusher et al ).…”
Section: Sources and Occurrence Of Microplastics In The Environmentmentioning
confidence: 99%
“…dyes), 28% were identified as plastic polymers (ESM 6) and around half (48%) of the particles were unidentifiable or were natural substances. This proportion of identified versus unidentified particles is common in aquatic microplastic studies using Raman spectroscopy (identified 41-67%) (Ballent et al 2016;Clunies-Ross et al 2016;Frère et al 2017). Because of the low number and size of microplastics found, and the ubiquity of microfibres found in urban atmospheres, contamination during coring and processing (Woodall et al 2015;Wesch et al 2017) must be acknowledged as a possible source of error.…”
Section: Methodsological Limitationsmentioning
confidence: 98%
“…The comparison of identification success rates between studies remained complicated as the number of analyzed MP and the identification methods were different. The rate of successful identification may be for example 57.5 % in a New Zealand study (Clunies-Ross et al 2016) or 4.5 % in a European study (Lots et al 2017).…”
Section: Particles Identificationmentioning
confidence: 99%